Methylmalonic Acidemia and Extrapyramidal Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Four children, 4-13 yrs old, with methylmalonic acidemia who developed acute dystonia after metabolic decompensation with ketoacidosis are reported from the Department of Pediatrics, University of Pennsylvania School of Medicine, and the Children's Hospital of Philadelphia, PA, and other collaborating institutions.